From Clause to Function: Texts Analysis Using Systemic Functional Linguistics Theory and Its Pedagogical Implication in Language Teaching - Hieronimus Canggung Darong (Indonesian Journal of EFL and Linguistics, 2021)
Using Systemic Functional Linguistics (SFL) theory, this study was an attempt to investigate the metafunctions of language which are realized by register category of field, tenor, and mode existing simultaneously in texts. Employing qualitative approach with the use of discourse semantics analysis, two different selected newspaper texts were purposefully chosen as the source of data. Following the orientation of SFL, the writer modified the texts into some sentences and clauses which were subsequently analysed and compared regarding the objectives in question. The result of analysis shows that the field of texts was mostly concerned with physical actions and events employing both direct and indirect speech for the sake of information. Meanwhile, in terms of mode, Text I was more rhetoric and more detail in describing the event than text II. Yet, the level of modality in both texts was low and low in which there were not many actions of getting other people to do things. Aside from those two, this analysis revealed that the mode of both texts mostly used anaphoric types of referential cohesion indicating written mode. In the meantime, Text I had more number of conjunctions implying more explanative in giving information and cause and effect relation of the information. Of greater importance of this finding was that a paradigmatic description of context implying a meaning, system, and metafunctions of language and its pedagogical implication in language teaching.